ANALISA KUALITAS AIR SUMUR GALI DI KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Anisyah Anisyah; Adrias Mashuri; Abdul Haris; Krisdianto Krisdianto (Universitas Lambung Mangkurat, 2013)
Water is very important for the livelihood of humans, animals and plants. With the increasing population growth, especially in densely populated urban areas, the need for water also increases, while the source of clean water that meets health requirements increasingly difficult obtained. One of the most commonly used is to dig the wells, but the dug wells easily contaminated. This study aims to: (1) Knowing the quality of dug well water from the parameters of physical, chemical and bacteriological in Banjarbaru City. (2) Knowing the factors that affect water quality of dug wells in Banjarbaru City. The method Purposive sampling of certain places which is considered important has been used in this study. Sampling was carried out by several criteria that have representation from dug wells, then in each sub-sample is selected so that the number of samples for the five districts are 20 samples. The analysis of dug well water based on the parameters of physics, chemistry and bacteriology. From the results of laboratory tests of the twenty selected sample representing the five districts in Banjarbaru City, it show that the condition of dug well water, based on Ministerial Decree of Environment (KEPMEN L.H) No. 115 year of 2003, the overall status of water quality of dug wells as follows: six sites meet on standart water quality (Good), ten light polluted, two locations are being polluted and two sites heavily polluted. Based on the analysis of data on the five study sites, it can be concluded that the water quality of dug wells in Banjarbaru is less fit for use as a quality standard for clean water has exceeded the threshold value of the raw water quality class I defined Minister of Health (PERMENKES) RI No. 416 / MENKES/PER/IX/1990 about Water Quality Requirements List. The need for attention to areas that have the potential for contamination of dug well water for the management and quality control measures water of dug wells consumed by the public.